2007
DOI: 10.3201/eid1307.061557
|View full text |Cite
|
Sign up to set email alerts
|

Human Influenza A (H5N1) Cases, Urban Areas of People’s Republic of China, 2005–2006

Abstract: We investigated potential sources of infection for 6 confirmed influenza A (H5N1) patients who resided in urban areas of People’s Republic of China. None had known exposure to sick poultry or poultry that died from illness, but all had visited wet poultry markets before illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 9 publications
1
41
0
Order By: Relevance
“…Horby and others the reported exposure to infected poultry is tenuous [17,[20][21][22]. The largest case-control study published so far found that only 28% of all cases could be attributed to preparing or cooking sick poultry [17].…”
mentioning
confidence: 99%
“…Horby and others the reported exposure to infected poultry is tenuous [17,[20][21][22]. The largest case-control study published so far found that only 28% of all cases could be attributed to preparing or cooking sick poultry [17].…”
mentioning
confidence: 99%
“…Live poultry markets have been speculated to be a major risk factor for human infection. Based on a retrospective epidemiology study, it was recently reported that most patients in urban areas in China during 2005 and 2006 visited live bird markets (32). However, there has been a lack of direct evidence showing an association between human isolates and those from live poultry markets.…”
mentioning
confidence: 99%
“…Equally, the authorities could consider whether to take a precautionary approach and implementation of countermeasures at an early stage, for example by giving more priority to hygiene in hospitals and rational approaches to antimicrobial prescribing. However, historical events including developments like SARS and highly pathogenic avian influenza in China indicate that to some extent future events in infectious diseases can never be entirely anticipated [7,10]. Hence it is crucial to establish basic surveillance and response mechanisms in a strong modern public health framework that can detect and respond to whatever threats should appear in the future.…”
Section: Lessons From This Applicationmentioning
confidence: 99%